Tracheal A‐Frame Deformities Following Airway Reconstruction. (26th August 2020) - Kennedy, Aimee A.; de Alarcon, Alessandro; Tabangin, Meredith E.; Rutter, Michael J.; Myer, Charles M.; Smith, Matthew M.; Hart, Catherine K.
Abstract : Objectives: Airway reconstruction for subglottic and tracheal stenosis is often successful in achieving tracheostomy decannulation and improving airway symptoms. However, one common reason for late failure is development of a tracheal A‐frame deformity, which can necessitate additional surgery. Although knowledge of this deformity exists, the incidence and risk factors have not been reported. This study seeks to determine the incidence of A‐frame following airway reconstruction and define factors that correlate with development of this deformity. Study Design: Retrospective case series. Methods: Patients under 21 years of age undergoing open airway reconstruction at our institution between January 2005–December 2006 were retrospectively reviewed. Demographic data, comorbidities, airway history/reconstruction type, and follow‐up airway findings were examined using multivariable logistic regression. Kaplan–Meier curves were used to examine time to A‐frame repair. Results: Two hundred patients underwent airway reconstruction and 69 (34.5%) developed an A‐frame deformity. History of tracheostomy was the most significant contributor to A‐frame development ( P < .0001). Double‐ versus single‐stage procedures were not associated with increased odds of A‐frame development ( P = .94), however, patients undergoing resection procedures as opposed to laryngotracheal reconstruction (LTR) with cartilage grafts had a significantly lower chance of developing this deformity ( P = .004). Of the patients with an A‐frame, 27 (39%) required further surgical intervention. Conclusion: Approximately one‐third of patients undergoing airway reconstruction developed a tracheal A‐frame deformity, with a significantly higher rate among patients with a history of tracheostomy and those undergoing LTR. Patients should be followed long term to assess for the development of an A‐frame. Level of Evidence: IV Laryngoscope, 131:E1363–E1368, 2021